2018
DOI: 10.1530/erc-17-0449
|View full text |Cite
|
Sign up to set email alerts
|

The impact of 27-hydroxycholesterol on endometrial cancer proliferation

Abstract: Endometrial cancer (EC) is the most common gynaecological malignancy. Obesity is a major risk factor for EC and is associated with elevated cholesterol. 27-hydroxycholesterol (27HC) is a cholesterol metabolite that functions as an endogenous agonist for Liver X receptor (LXR) and a selective oestrogen receptor modulator (SERM). Exposure to oestrogenic ligands increases risk of developing EC; however, the impact of 27HC on EC is unknown. Samples of stage 1 EC (n = 126) were collected from postmenopausal women u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 35 publications
0
17
1
Order By: Relevance
“…Previous studies showed that, E1, but not E2, significantly decreases proliferation when added exogenously to the colonic epithelial cell line, SW620 cells [51]. In different cell models however, 27-OHC has been shown to increase proliferation in endometrium through ER and LXR pathways [52]. Although we show a decrease in cell proliferation, the cellular mechanisms by which 27-OHC affects proliferation is yet to be determined.…”
Section: Discussioncontrasting
confidence: 46%
“…Previous studies showed that, E1, but not E2, significantly decreases proliferation when added exogenously to the colonic epithelial cell line, SW620 cells [51]. In different cell models however, 27-OHC has been shown to increase proliferation in endometrium through ER and LXR pathways [52]. Although we show a decrease in cell proliferation, the cellular mechanisms by which 27-OHC affects proliferation is yet to be determined.…”
Section: Discussioncontrasting
confidence: 46%
“…Insulin can activate the phosphoinositide 3kinase/protein kinase B or mitogen-activated protein kinase/extracellular signal-regulated kinase signaling pathway by binding to insulin receptor/insulin-like growth factor-1 receptor, thereby promoting epithelialmesenchymal transition and increasing the proliferation and invasion of EC cells [27]. Furthermore, a recent study has reported that cholesterol can activate the transcriptional activity of EC cells and promote the proliferation of EC cells [28].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, using kinase inhibitors, we demonstrated that the effect of 27HC was mediated by the PI3K-Akt signaling pathway [ 26 ]. Another group working on endometrial cancer, the most common gynecological malignancy, showed that 27HC contributes to the risk of endometrial cancer by promoting the proliferation of endometrial cancer epithelial cells and also the activation of ER-dependent transcription in well-differentiated endometrial cancer cells [ 91 ]. A recent study demonstrated the effects of 27HC on colorectal cancer, the third most diagnosed cancer in the western world [ 91 ].…”
Section: 27hc and Other Cancersmentioning
confidence: 99%
“…Another group working on endometrial cancer, the most common gynecological malignancy, showed that 27HC contributes to the risk of endometrial cancer by promoting the proliferation of endometrial cancer epithelial cells and also the activation of ER-dependent transcription in well-differentiated endometrial cancer cells [ 91 ]. A recent study demonstrated the effects of 27HC on colorectal cancer, the third most diagnosed cancer in the western world [ 91 ]. Treating Caco2 and SW620 colon cancer cells with 27HC led to a reduced cellular proliferation.…”
Section: 27hc and Other Cancersmentioning
confidence: 99%